Cannabis use, perceived problems and the contemplation of reducing or quitting: a cross-sectional survey for vocational students - Lostedt, Jasmin (Taylor & Francis, 2025)
Objective: To assess problematic cannabis use, perceived cannabis-related problems and contemplation of reducing or quitting the use among vocational students and associations between perceived problems and contemplation of reducing or quitting cannabis use.
Methods: A cross-sectional survey among Finnish vocational school students (N = 1,855) using the Cannabis Use Disorder Identification Test-Revised.
Results: Of those who reported cannabis use (n = 375), 20.5% (n = 77) reported problematic use. The most perceived problems were memory or concentration problems (n = 151, 39.1%), devoting a great deal of time to use (n = 144, 37.4%), and failing to do what was normally expected (n = 106, 27.5%). One third (35.4%, n = 136) had contemplated reducing or quitting the use, especially among those who reported an inability to stop using (Adjusted odds ratio (AOR): 5.57; CI95: 2.48–13.16).
Conclusions: The perceived problems related to cannabis-use are such that may affect to academic success, employment and general life management. It is imperative to screen and implement low- threshold cannabis interventions in student health care. A third of students who used cannabis had contemplated quitting or reducing use, which provides an opportunity for brief supporting interventions.